(untitled) (International Journal of Physiotherapy, 2016)
Background: Patient benefit from repair of pectus excavatum has mainly been considered psychological although some evidence of physiological benefit has emerged. The purpose of this study was to investigate lung function, respiratory movement and physical fitness together with the patient’s satisfaction with the look of the chest one year following modified Nuss procedure. Methods: In this prospective cohort follow-up study eighteen boys and young men who underwent modified Nuss procedure participated. Measurements of lung volumes using spirometry, respiratory movements using Respiratory Movement Measuring Instrument, and physical fitness using Aastrand ergometer bicycle test were performed pre- and one year post-operatively. Assessment of participants’ opinion of the looks of their chest was made at the same point in time. Results: Participants mean age was 16±3 years, their mean BMI was 20.8±3.5 kg/m2 and mean Haller Index was 3.9±0.7. Significant changes one year following modified Nuss procedure were found in mean abdominal- and upper thoracic respiratory movements during deep breathing (p≥0.001, p≥0.05, respectively), mean physical fitness (p=0.01) and mean satisfaction with chest looks in general and without shirt (p=0.03, p=0.001 respectively). Conclusion: Increased physical fitness, abdominal- and upper thoracic respiratory movements one year following modified Nuss procedure together with high level of patient satisfaction supports the argument that patients benefit from undergoing the repair is physical as well as cosmetic.